RANCANG BANGUN SISTEM E-LIBRARY BERBASIS WEB DI SMK BINAKARYA MANDIRI BEKASI - Satria; Indy Khusnayeni; Belinda Eka Sarah Dewi; Marisa; Carudin; Panca Indah Lestari (LPPM Universitas Bani Saleh, 2025)
The development of information technology has encouraged various educational institutions to shift from manual systems to more effective and efficient digital systems. Library management is one important aspect that requires digitalization so that the process of recording, information retrieval, and service to users can run more optimally. To support these needs, this study designed a web-based E-Library system with the aim of improving the quality of library services, providing faster access to information, and facilitating collection management and borrowing activities. This study used a prototype method with data collection techniques through observation, interviews, and document studies. The system was developed using the CodeIgniter framework, PHP, MySQL, and UML design, then tested using Black Box Testing. The results of the study indicate that the E-Library system built is able to improve the efficiency of library management, reduce administrative errors, accelerate the activity monitoring process, and provide digital book reading access for users. However, several limitations were still found, such as the lack of access rights settings for downloading e-books and the lack of a reading history feature, which are recommended for development in the next stage